Completing your PHD - Williams, Kate , 1949- (Pocket study skills, 2011)
Concise and well-presented, this guide will be invaluable to any Ph.D. student seeking to successfully complete their thesis. Based on students' direct experiences, topics include developing your argument, planning your time, editing, what examiners are looking for, talking about your research, and the viva